Evolutionary Rhetoric : Sex, Science, and Free Love in Nineteenth-Century Feminism - Hayden, Wendy, 1977- (Book collections on Project MUSE., 2013)
In this book, the author explores the relationship between scientific and feminist rhetorics in free-love feminism, studying the movement from its inception in the 1850s to its dark turn toward eugenics in the early 1900s. The author organizes her provocative study by scientific discipline - evolution, physiology, bacteriology, embryology, and heredity. Each chapter explores how free-love feminists adopted the evidence of that discipline in their arguments for increased sex education, women's sexual rights, reproductive freedom, and the abolition of a marriage system that repressed the rights and the sexuality of women.